EFEKTIVITAS PELAKSANAAN PEMBELAJARAN DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Sinambela, Samuel Anugrah; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Study is trying to abtain to cleverness or science, exercising , changing of behavior or responded that because of experience. To reach learning qualified in need of learning effective and right targets . In achieving the effectiveness of study , need to obedience in the regulation of learning . The purpose of this research is for knowing effectiveness of Implementation learning at faculty of social and political science University of Riau,,and for knowing of factors in inhibitingting effectiveness of Implementation of learning at faculty of social and poltical science University of Riau. The teory that using in this reseach is teory of effevtiveness accroding Mamudi who consists of several indocator important is : Input, Process, Output, outcome , election of informan , the research using snowball sampling technique . Techinque of data in this research is with intrerview , observation and dokumentation. the reasult from this research is tah show learning at faculty of social and poltical science does not already effective because of still many indicators from regualtions dean that does not already good way .. In the this research has founded there are some factors inhibiting effectiveness of implemntation learning at FISIP UR is such as less human capital are the lecture , the afctive of student in studying and unmanageable the delegate was of the subjects that lasts for one semester . For that needed by add human capital are the lecture , the active of student in matery developing that given by lecture , and also need to discipline in regulation of implementation of learning .Key Words : Effectiveesss , Implementation of Learning